Optical laminate, optical laminate roll, and method for manufacturing polarizing plate
Patent Information
- Application Number
- JP2022201999
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-12-19
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2042-12-19
AI Technical Summary
【0008】 本発明の実施形態によれば、配向度の高い偏光子を含むにもかかわらず、製造工程において表面保護フィルムを剥離する際の剥離不良が抑制された光学積層体を実現することができる。
Smart Images

Figure 0007638258000002 
Figure 0007638258000003 
Figure 0007638258000004
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical laminate, a roll of an optical laminate, and a method for producing a polarizing plate. [Background technology]
[0002] In image display devices (e.g., liquid crystal display devices, organic electroluminescence display devices, quantum dot display devices), a polarizing plate is often arranged on at least one side of the display panel due to the image formation method. In recent years, there has been an increasing demand for narrower frame (in some cases, so-called bezel-less) image display devices, and there is an increasing need to prevent color loss (edge discoloration) at the edge of the polarizing plate. In order to suppress or prevent edge discoloration of the polarizing plate, a technology has been proposed that improves the durability of the polarizer, which essentially governs the optical properties of the polarizing plate, in a high-temperature and high-humidity environment. As such a technology, for example, a polarizer with a high degree of orientation has been considered.
[0003] Incidentally, a polarizing plate (or an optical film including a polarizing plate) is typically produced by laminating a polarizer and various optically functional layers according to the purpose. In many cases, a so-called roll-to-roll operation is employed for at least a part of the lamination. When lamination is performed in multiple stages, the widthwise end of the laminate may be slit at a predetermined stage. Furthermore, when lamination is performed in multiple stages, a surface protection film called a process SPV is often temporarily attached to the laminate in a peelable manner to protect the laminate, which is a precursor of the polarizing plate (or an optical film including a polarizing plate), from scratches and dirt.
[0004] When the highly oriented polarizer as described above is laminated and slit, cracks may be formed at the width direction end of the polarizer by the slit. When the surface protective film is peeled off from the highly oriented polarizer in which such cracks are formed, peeling failure may occur in which at least a part of the polarizer is peeled off from the laminate including the polarizer. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2020-160231 A [Patent Document 2] JP 2020-001382 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made to solve the above-mentioned conventional problems, and its main object is to provide an optical laminate in which peeling defects are suppressed when peeling off a surface protective film during the manufacturing process, despite containing a polarizer with a high degree of orientation. [Means for solving the problem]
[0007] [1] An optical laminate according to an embodiment of the present invention is long and includes a polarizer, a protective layer provided on one side of the polarizer, and a surface protective film temporarily attached in a peelable manner to the other side of the polarizer. The polarizer has an indentation hardness of 0.65 GPa or more, and a crack of 50 μm to 5000 μm is formed at an end of the polarizer in the width direction, and the extension direction of the crack is 30° to 150° with respect to the long direction. [2] In the above [1], the polarizer has an indentation elastic modulus of 9.5 GPa or less. [3] In the above [1] or [2], the orientation function of the polarizer is 0.30 or more. [4] According to another aspect of the present invention, there is provided a roll of an optical laminate, the roll of the optical laminate being formed by winding the optical laminate according to any one of [1] to [3] above. [5] According to yet another aspect of the present invention, there is provided a method for producing a polarizing plate, comprising: transporting the optical laminate of any one of [1] to [3] above or a roll of the optical laminate of [4] above in a longitudinal direction of the optical laminate; and peeling off the surface protective film while transporting the optical laminate; and peeling off the surface protective film in a state in which the extension direction of the crack forms an angle of 30° or more and less than 180° with respect to the transport direction. [6] In the above [5], the direction in which the crack extends is greater than 0° and less than 30° with respect to the conveying direction of the optical laminate, and the above manufacturing method includes rewinding the optical laminate to set the angle of the crack extension direction to an angle of 30° or more and less than 180° with respect to the conveying direction. Effect of the Invention
[0008] According to an embodiment of the present invention, it is possible to realize an optical laminate in which peeling defects are suppressed when peeling off a surface protective film in a production process, despite including a polarizer with a high degree of orientation. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1A is a schematic plan view of an optical laminate according to one embodiment of the present invention; FIG. 1B is a schematic cross-sectional view of the optical laminate of FIG. [Diagram 2] 1(a) is a schematic plan view showing an example of the relationship between the direction in which the end crack of a polarizer extends and the longitudinal direction and conveying direction of an optical laminate in an embodiment of the present invention; and FIG. 1(b) is a schematic plan view showing another example of the relationship. [Diagram 3] FIG. 2(a) is a side view of a cutting blade and a receiving blade of a slit blade that can be used in an embodiment of the present invention; FIG. 2(b) is an explanatory diagram showing how an optical laminate is cut by the slit blade. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Representative embodiments of the present invention will be described below with reference to the drawings, but the present invention is not limited to these embodiments. Note that the drawings are drawn in a schematic manner for ease of viewing, and do not accurately reflect actual lengths, widths, thicknesses, angles, ratios, etc.
[0011] A. Overall configuration of optical laminate FIG. 1(a) is a schematic plan view of an optical laminate according to one embodiment of the present invention; FIG. 1(b) is a schematic cross-sectional view of the optical laminate of FIG. 1(a) along line BB. FIG. 2(a) is a schematic plan view showing an example of the relationship between the direction in which the end crack of the polarizer extends and the longitudinal direction and transport direction of the optical laminate in an embodiment of the present invention; FIG. 2(b) is a schematic plan view showing another example of the relationship. The optical laminate 100 in the illustrated example is long and extends in the vertical direction of the drawing. Such a long optical laminate can be wound into a roll. Therefore, the optical laminate can be wound into a roll to form an optical laminate roll. The optical laminate 100 has a polarizer 11, a protective layer 12 provided on one side of the polarizer 11, and a surface protective film 20 temporarily attached in a peelable manner to the other side of the polarizer 11. In one embodiment, as shown in the illustrated example, the optical laminate 100 has, from the top, the protective layer 12, the polarizer 11, and the surface protective film 20. In another embodiment, the optical laminate may have a surface protective film, a polarizer, and a protective layer in this order from the top. A crack 50 is formed at the width direction end of the polarizer 11. The crack may be formed, typically, due to a slit in a previous process. In other words, the optical laminate according to the embodiment of the present invention has a slit at the width direction end. The size (length) of the crack is 50 μm to 5000 μm, and the direction in which the crack extends is 30° to 150° with respect to the longitudinal direction. According to the embodiment of the present invention, even if a crack is formed at the end of a polarizer having a high degree of orientation as described below, peeling failure can be significantly suppressed by controlling the direction in which the crack extends. In this specification, the term "peeling failure" refers to a phenomenon in which not only the surface protective film but also at least a part of the polarizer peels off when the surface protective film is peeled off from the optical laminate. Since the crack in the embodiment of the present invention may be formed due to a slit in a previous process as described above, the direction in which the crack extends is maintained within a predetermined range. For example, 90% or more of the cracks extend in a direction typically within ±20°, preferably within ±10°, and more preferably within ±5° of the median direction (the average angle that all the cracks make with the longitudinal direction).Therefore, the direction in which the crack extends can be controlled by adjusting the slit conditions. The direction in which the crack extends should not deviate from the range of 30° to 150° with respect to the longitudinal direction, so that in the embodiment of the present invention, variations within this range are not a problem. For example, when inspecting the end face of an optical laminate with a length of 10 cm cut out at random, if the extension direction of all cracks recognized is within the range of 30° to 150° with respect to the longitudinal direction, peeling failure can be suppressed even if the extension direction of the crack deviates significantly (for example, beyond ±20°) from the center value of the above direction. In this specification, unless otherwise specified, the extension direction of the crack is the direction when the optical laminate is viewed from the top.
[0012] The size (length) of the crack is preferably 50 μm to 3500 μm, more preferably 50 μm to 2000 μm. When the size of the crack is small (for example, less than 50 μm), peeling failure often does not occur. The upper limit of the size of the crack formed by the slit in the previous process is sufficiently smaller than the margin required in the subsequent process (the part finally removed by the slit), so there is practically no technical meaning in specifying the upper limit. The effect of the embodiment of the present invention can be exhibited as long as the direction in which the crack extends is within the above-mentioned range (30° to 150° with respect to the longitudinal direction). The direction in which the crack extends may be, for example, 35° or more, or, for example, 40° or more, or, for example, 45° or more, or, for example, 50° or more, or, for example, 60° or more, or, for example, 70° or more. On the other hand, the direction in which the crack extends may be, for example, 145° or less, or, for example, 140° or less, or, for example, 135° or less, or, for example, 130° or less, or, for example, 120° or less, or, for example, 110° or less.
[0013] With reference to FIG. 2(a) and FIG. 2(b), the relationship between the direction in which the crack extends and the longitudinal direction and transport direction of the optical laminate will be specifically described. As described above, the direction in which the crack 50 extends (angle θ) is 30° to 150° with respect to the longitudinal direction of the optical laminate. The longitudinal direction of the optical laminate substantially corresponds to the transport direction of the optical laminate (arrow 30 in the figure). When the angle θ is an acute angle as shown in FIG. 2(a), the direction in which the crack 50 extends is the forward direction with respect to the transport direction 30; when the angle θ is an obtuse angle as shown in FIG. 2(b), the direction in which the crack 50 extends is the reverse direction with respect to the transport direction 30. When the angle θ is 90° (right angle), the direction in which the crack 50 extends is the direction perpendicular to the transport direction (width direction).
[0014] In the embodiment of the present invention, the indentation hardness of the polarizer 11 is 0.65 GPa or more. Furthermore, the indentation elastic modulus of the polarizer 11 is typically 9.5 GPa or less, and the orientation function is typically 0.30 or more. When such a hard polarizer with a high degree of orientation is used, the effect of the embodiment of the present invention is remarkable. Specifically, even if cracks are formed in such a polarizer with a high degree of orientation, peeling failure can be significantly suppressed when peeling the surface protective film from the optical laminate.
[0015] Hereinafter, a method for forming cracks at the polarizer end will be described. As described above, the cracks can be formed by slitting in the previous process (removal of the width direction end by cutting). As described above, the direction in which the cracks extend can be controlled by adjusting the slitting conditions. Examples of the slitting conditions include the taper angle of the cutting edge of the slitting blade, the conveying tension during slitting, the take-up tension of the slit film end, the state of the slitting blade, and the overlap length of the slitting blade. Hereinafter, an example of a specific slitting procedure will be described.
[0016] FIG. 3(a) is a side view of a cutting blade and a receiving blade of a slit blade that can be used in an embodiment of the present invention; FIG. 3(b) is an explanatory diagram showing the state of cutting an optical laminate by a slit blade. As shown in FIG. 3(a) and FIG. 3(b), an optical laminate 100 is cut using a cutting blade 1 and a receiving blade 2 for supporting the optical laminate 100. The cutting blade 1 and the receiving blade 2 are supported so that their blade tips partially overlap each other. The overlap length L is set, for example, according to the thickness of the optical laminate to be cut. It is preferable that the overlap length L satisfies the relationship d≦L≦d+0.15 mm with respect to the thickness d (mm) of the optical laminate. The overlap length L is, for example, 0.2 mm to 2.0 mm. The cutting blade axis 1a and the receiving blade axis 2a are arranged so as to be parallel to the optical laminate 100. The optical laminate 100 is slit (cut) into a strip-like shape at the width direction end by passing between the cutting blade 1 and the receiving blade 2. The conveying speed of the optical laminate 100 can be set, for example, in the range of 10 m / min to 50 m / min.
[0017] The receiving blade 2 is not fixed to the receiving blade shaft 2a and rotates freely (for example, counterclockwise). The cutting blade 1 is attached to the cutting blade shaft 1a by a spring bias so as to contact the receiving blade 2 by any appropriate support mechanism, and rotates together with the cutting blade shaft 1a (for example, clockwise). The contact pressure between the cutting blade and the receiving blade is set, for example, according to the shape of the blade described later. The contact pressure between the cutting blade and the receiving blade is, for example, 2.0N to 10.0N. The rotation speed of the cutting blade is preferably approximately the same as the conveying speed of the optical laminate or faster than the conveying speed of the optical laminate. Specifically, the rotation speed of the cutting blade is set, for example, to 90% to 130% of the conveying speed of the polarizing film laminate, preferably 95% to 130%, and more preferably 98% to 130%.
[0018] The outer diameter of the cutting blade and the receiving blade is, for example, 90.0 mm to 110.0 mm. The receiving blade 2 has a wide cutting edge as shown in the figure in order to support the optical laminate 100 at the cutting position. In the illustrated example, one side 1b of the cutting blade 1 is a vertical surface, and the other side 1c is a tapered surface. The taper angle of the tapered surface may be, for example, 35° to 85°, or may be, for example, 40° to 60°, or may be, for example, 60° to 85°. By adjusting the taper angle, the direction in which the crack extends can be controlled. The cut pieces are removed, for example, by winding or suction.
[0019] In the illustrated example, the cutting blade 1 is positioned so that the relatively thick portion of the tapered cutting blade 1 that gradually narrows toward the cutting edge faces the protective layer 12 and the relatively thin portion faces the surface protective film 20, and the cutting edge of the cutting blade 1 is in contact with the optical laminate 100, but the optical laminate may be upside down. That is, the cutting blade 1 may be positioned so that the relatively thick portion of the cutting blade 1 faces the surface protective film 20 and the relatively thin portion of the cutting blade 1 faces the protective layer 12, and the cutting edge of the cutting blade 1 is in contact with the optical laminate 100.
[0020] The conveying tension during slitting of the optical laminate is preferably 220N or more, more preferably 270N or more, even more preferably 300N or more, and particularly preferably 320N or more. If the conveying tension is in this range, the direction of crack extension can be set to the desired direction by adjusting the taper angle of the cutting edge of the slit blade in combination. The upper limit of the conveying tension can be, for example, 400N.
[0021] B. Polarizer As described above, the polarizer 11 has an indentation hardness of 0.65 GPa or more. The indentation hardness of the polarizer is preferably 0.65 GPa to 0.80 GPa, more preferably 0.66 GPa to 0.76 GPa, further preferably 0.67 GPa to 0.74 GPa, and particularly preferably 0.68 GPa to 0.72 GPa. That is, the polarizer used in the embodiment of the present invention is very hard. Such a polarizer can significantly suppress edge discoloration in a high-temperature and high-humidity environment. As a result, such a polarizer can be suitably used in an image display device with a narrow frame (in some cases, so-called bezel-less). As described above, when such a hard polarizer is used, the effect of the embodiment of the present invention is remarkable.
[0022] The polarizer typically has an indentation modulus of 9.5 GPa or less, preferably 7.5 GPa to 9.4 GPa, more preferably 8.0 GPa to 9.3 GPa, further preferably 8.2 GPa to 9.2 GPa, and particularly preferably 8.5 GPa to 9.2 GPa. The polarizer used in the embodiment of the present invention has a relatively low indentation modulus despite being very hard as described above. Such a polarizer can be easily stretched while maintaining the advantage of its hardness (suppression of edge discoloration), and therefore can be easily thinned.
[0023] The indentation hardness and the indentation modulus can be typically measured by a nanoindentation method using an indentation tester (typically, a nanoindenter). More specifically, the indentation hardness is calculated from the maximum load Pmax obtained from a displacement-load hysteresis curve obtained by pressing a probe (indenter) against the surface of the polarizer to be measured, and the contact projected area A between the indenter and the polarizer, according to the following formula: Indentation hardness (GPa) = Pmax / A The indentation elastic modulus is calculated from the above-mentioned contact projection area A, the slope of the tangent to the unloading curve of the displacement-load hysteresis curve (contact stiffness) S, and the circular constant π, according to the following formula: Indentation modulus (GPa) = (√π / 2) × (S / √A)
[0024] The orientation function of the polarizer is preferably 0.30 or more, more preferably 0.35 or more, even more preferably 0.37 or more, and particularly preferably 0.40 or more. If the orientation function of the polarizer is in such a range, it is easy to set the indentation elastic modulus and indentation hardness to the desired range. The upper limit of the orientation function of the polarizer can be, for example, 0.50. The orientation function (y) is determined, for example, by attenuated total reflection (ATR) measurement using a Fourier transform infrared spectrophotometer (FT-IR) and polarized light as the measurement light. Specifically, the measurement is performed with the stretching direction of the polarizer parallel and perpendicular to the polarization direction of the measurement light, and the 2941 cm of the obtained absorbance spectrum is measured. -1 The intensity I is calculated according to the following formula using the intensity of 3330 cm -1 is used as the reference peak, and 2941 cm -1 / 3330cm -1 The value is 2941 cm. Note that y=1 is perfect alignment, and y=0 is random. -1 The peak is due to the main chain (-CH) of PVA in the polarizer. 2 It is believed that this absorption is due to vibrations of the -. y=(3 <cos 2 θ>-1) / 2 =(1-D) / [c(2D+1)] =-2×(1-D) / (2D+1) however, c = (3cos 2 β-1) / 2, 2941cm -1 For vibration, β=90°. θ: Angle of molecular chain to stretching direction β: Angle of the transition dipole moment with respect to the chain axis D=(I ⊥ ) / (I / / ) (In this case, the more the PVA molecules are oriented, the larger D becomes.) I ⊥ : Absorption intensity when the polarization direction of the measurement light and the stretching direction of the polarizer are perpendicular I / / : Absorption intensity when the polarization direction of the measurement light and the stretching direction of the polarizer are parallel
[0025] The polarizer may have any suitable structure as long as it has the above-mentioned characteristics. Typically, the polarizer is made of a polyvinyl alcohol (PVA)-based resin film containing a dichroic material (e.g., iodine). Examples of PVA-based resins include polyvinyl alcohol, partially formalized polyvinyl alcohol, ethylene-vinyl alcohol copolymer, and partially saponified ethylene-vinyl acetate copolymer.
[0026] The PVA-based resin preferably contains an acetoacetyl-modified PVA-based resin. With this configuration, a polarizer having desired mechanical strength can be obtained. The amount of the acetoacetyl-modified PVA-based resin is preferably 5% by weight to 20% by weight, and more preferably 8% by weight to 12% by weight, based on 100% by weight of the entire PVA-based resin. If the amount is within this range, a polarizer having better mechanical strength can be obtained.
[0027] The polarizer preferably contains iodide or sodium chloride (sometimes collectively referred to as halide). Examples of iodide include potassium iodide, sodium iodide, and lithium iodide. The content of the halide in the polarizer is preferably 5 to 20 parts by weight, more preferably 10 to 15 parts by weight, based on 100 parts by weight of the PVA-based resin. In the manufacturing method described below, the halide can be blended in a coating liquid that forms a PVA-based resin layer, which is a precursor of the polarizer, and finally introduced into the polarizer. By introducing a halide into the polarizer, the orientation of the PVA molecules in the polarizer can be increased, so that a desired orientation function and indentation hardness can be realized. Furthermore, a polarizer having excellent optical properties (typically, both a high polarization degree and a high single transmittance) can be realized.
[0028] The iodine concentration of the polarizer is preferably 4% by weight to 10% by weight, and more preferably 5.5% by weight to 8% by weight. In this specification, the term "iodine concentration" means the total amount of iodine contained in the polarizer. More specifically, iodine in the polarizer is I - , I 2 , I 3 - , I 5 - In this specification, the iodine concentration refers to the concentration of iodine including all of these forms. The iodine concentration can be calculated, for example, from the fluorescent X-ray intensity by fluorescent X-ray analysis and the film (polarizer) thickness.
[0029] The thickness of the polarizer is preferably 1 μm to 8 μm, more preferably 2 μm to 7 μm, and further preferably 3 μm to 6 μm. When the thickness of the polarizer is within this range, curling during heating can be well suppressed, and good appearance durability during heating can be obtained.
[0030] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is, for example, 41.0% to 45.0%, preferably 41.5% to 43.5%, and more preferably 42.0% to 43.0%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more. According to the embodiment of the present invention, even if the single transmittance is in the above-mentioned range, the degree of polarization can be maintained in such a range.
[0031] A polarizer can be obtained, typically, by using a laminate of a resin substrate and a PVA-based resin layer. Specific examples of polarizers obtained by using a laminate include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained by using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. A polarizer obtained by using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be produced, for example, by applying a PVA-based resin solution to the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, preferably, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch it. Furthermore, the stretching may further include air-stretching the laminate at a high temperature (for example, 95°C or higher) before stretching in the boric acid aqueous solution, as necessary. In addition, in this embodiment, the laminate is preferably subjected to a drying shrinkage treatment in which the laminate is heated while being conveyed in the longitudinal direction, thereby shrinking the laminate by 2% or more in the width direction. Typically, the manufacturing method of this embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, it is possible to increase the crystallinity of PVA even when PVA is applied onto a thermoplastic resin, and it is possible to achieve high optical properties. At the same time, by increasing the orientation of PVA in advance, problems such as a decrease in the orientation or dissolution of PVA can be prevented when the PVA is immersed in water in the subsequent dyeing step or stretching step, and it is possible to achieve high optical properties. Furthermore, when the PVA-based resin layer is immersed in a liquid, the disturbance of the orientation of polyvinyl alcohol molecules and the decrease in orientation can be suppressed compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of a polarizer obtained by immersing the laminate in a liquid in a treatment process such as a dyeing process and an underwater stretching process, etc. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction by a drying shrinkage process.The obtained resin substrate / polarizer laminate may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or any suitable protective layer may be laminated on the peeled surface of the resin substrate / polarizer laminate after peeling the resin substrate from the resin substrate / polarizer laminate, or on the surface opposite to the peeled surface, depending on the purpose. Details of the method for producing such a polarizer are described in, for example, JP2012-73580A and JP6470455A. The entire disclosures of these publications are incorporated herein by reference.
[0032] The above-mentioned hard polarizer having a high degree of orientation can be obtained by performing the auxiliary air-stretching process at a higher temperature and a higher stretching ratio than in the past. Preferably, the stretching temperature in the auxiliary air-stretching process is 140°C or higher, and the stretching ratio is 2.5 times or higher. The stretching temperature is more preferably 145°C or higher, further preferably 150°C or higher, and particularly preferably 155°C or higher. The upper limit of the stretching temperature can be, for example, 170°C. The stretching ratio is more preferably 2.5 times to 3.2 times, further preferably 2.6 times to 3.1 times, and particularly preferably 2.7 times to 3.0 times. In the conventional method for producing a thin polarizer, the auxiliary air-stretching process is typically performed at a temperature that is 15°C higher than the glass transition temperature (Tg) of the thermoplastic resin substrate (typically, polyethylene terephthalate (PET)) and that can suppress rapid crystallization of the PVA-based resin. Specifically, such a stretching temperature is around 130°C. In addition, the stretching ratio of the auxiliary air stretching process in the conventional method for producing a thin polarizer is usually set to 2.0 to 2.4 times. Since the total stretching ratio of the auxiliary air stretching process and the underwater stretching process is preferably constant (for example, 5.5 to 6.0 times), when stretching at around 130°C, the stretching ratio of the underwater stretching process needs to be reduced at a stretching ratio exceeding 2.5 times, and the optical properties may be deteriorated due to the decrease in the orientation of iodine. In addition, at a temperature exceeding 130°C, it is difficult to suppress the rapid crystallization of the PVA-based resin as described above, and further, it is difficult to control the stretchability. The present inventors have found that a hard thin polarizer can be realized while maintaining the desired optical properties (achieving both a high single transmittance and a high polarization degree) by performing the auxiliary air stretching process at a high temperature and a high stretching ratio that have not been performed in the past.
[0033] C. Protective layer The protective layer 12 is composed of any suitable resin film that can be used as a protective film for a polarizer. Representative materials for the resin film include cellulose-based resins such as triacetyl cellulose (TAC), cycloolefin-based resins such as polynorbornene, (meth)acrylic resins, polyester-based resins such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), polyolefin-based resins such as polyethylene, and polycarbonate-based resins. Representative examples of (meth)acrylic resins include (meth)acrylic resins having a lactone ring structure. (Meth)acrylic resins having a lactone ring structure are described in, for example, JP-A-2000-230016, JP-A-2001-151814, JP-A-2002-120326, JP-A-2002-254544, and JP-A-2005-146084. These publications are incorporated herein by reference. From the viewpoint of ease of processing into irregular shapes, etc., cellulose-based resins are preferred, and TAC is more preferred. From the viewpoint of obtaining a polarizing plate having low moisture permeability and excellent durability, cycloolefin-based resins and (meth)acrylic resins are preferred.
[0034] The protective layer 12 may be subjected to a surface treatment as required. Examples of the surface treatment include a hard coat treatment, an anti-reflection treatment, an anti-sticking treatment, and an anti-glare treatment. In addition, the protective layer 12 may be subjected to a treatment for improving visibility when viewed through polarized sunglasses (typically, imparting an (elliptical) polarization function or imparting an ultra-high phase difference) as required. By performing such a treatment, excellent visibility can be achieved even when the display screen is viewed through polarized lenses such as polarized sunglasses. Therefore, the optical laminate can be suitably applied to an image display device that can be used outdoors.
[0035] The thickness of the protective layer 12 is preferably 10 μm to 80 μm, more preferably 12 μm to 40 μm, and further preferably 15 μm to 35 μm. When a surface treatment is applied, the thickness of the protective layer includes the thickness of the surface treatment layer.
[0036] D. Surface protection film The surface protection film 20 typically has a substrate and an adhesive layer, and is temporarily attached to the polarizer via the adhesive layer in a peelable manner. The substrate may be made of any appropriate material. As the constituent material, a material having isotropy or close to isotropy may be used from the viewpoint of inspectability and manageability. Specific examples of the constituent material include transparent polymers such as polyester-based resins such as polyethylene terephthalate film, cellulose-based resins, acetate-based resins, polyethersulfone-based resins, polycarbonate-based resins, polyamide-based resins, polyimide-based resins, polyolefin-based resins, and acrylic-based resins. Among these, polyolefin-based resins are preferred. The substrate may be a laminate of one or more constituent materials, or may be a stretched film.
[0037] Examples of polyolefin resins include homopolymers of olefin monomers and copolymers of olefin monomers. Specific examples of polyolefin resins include polyethylene resins such as high density polyethylene (HDPE), medium density polyethylene, low density polyethylene (LDPE), and linear low density polyethylene (LLDPE); polypropylene; propylene copolymers such as block, random, and graft copolymers with ethylene as a copolymerization component; reactor TPO; ethylene copolymers such as ethylene-vinyl acetate copolymers, ethylene-methyl acrylate copolymers, ethylene-ethyl acrylate copolymers, ethylene-butyl acrylate copolymers, ethylene-methacrylic acid copolymers, and ethylene-methyl methacrylate copolymers, among which polyethylene resins are preferred.
[0038] The thickness of the substrate can be appropriately set depending on the purpose, and is, for example, 200 μm or less, and preferably 10 to 150 μm.
[0039] Any suitable adhesive can be used as the adhesive constituting the adhesive layer. The thickness (dry film thickness) of the adhesive layer is preferably 1 μm to 100 μm, more preferably 5 μm to 50 μm. If the thickness is within this range, a desired peel strength can be achieved for the polarizer.
[0040] If necessary, a release treatment layer may be provided on the surface of the substrate opposite to the pressure-sensitive adhesive layer. The release treatment layer may be a surface treatment layer made of a low-adhesion material such as silicone, long-chain alkyl, or fluorine.
[0041] A commercially available product may be used as the surface protection film. As a commercially available product, Toraytec 7832C #30 manufactured by Toray Advanced Film Co., Ltd. can be suitably used.
[0042] The peel strength between the polarizer and the surface protective film is preferably 0.01 N / 10 mm to 5.0 N / 10 mm, more preferably 0.01 to 0.5 N / 10 mm, and further preferably 0.035 to 0.1 N / 10 mm. The peel strength can be measured, for example, in accordance with JIS Z 0237.
[0043] The initial peeling force when peeling off the surface protective film may be, for example, 2.0N or less, for example, 1.5N or less, for example, 1.2N or less, for example, 1.0N or less, for example, 0.8N or less, for example, 0.7N or less, for example, 0.6N or less, or for example, 0.5N or less. The lower limit of the initial peeling force may be, for example, 0.05N. If the initial peeling force is in such a range, the surface protective film can be easily peeled off, and peeling failure can be significantly suppressed. The initial peeling force may be measured, for example, according to JIS Z 0237. Specifically, a pick-up tape is attached to the surface of the surface protective film of the test sample (optical laminate) along the peeling direction, and the peeling force when the pick-up tape is used to peel off at a tensile direction of 90° can be measured as the initial peeling force. The width of the pick-up tape may be, for example, 10 mm, and the pulling speed may be, for example, 300 mm / min.
[0044] E. Manufacturing method of polarizing plate The optical laminate according to the embodiment of the present invention described in the above items A to D is an intermediate of a polarizing plate or an optical film including a polarizing plate. In other words, a polarizing plate or an optical film including a polarizing plate can be manufactured using the optical laminate according to the embodiment of the present invention. Therefore, the manufacturing method of a polarizing plate using the optical laminate according to the embodiment of the present invention is also included in the embodiment of the present invention.
[0045] A method for producing a polarizing plate according to an embodiment of the present invention includes: transporting an optical laminate according to an embodiment of the present invention described above in items A to D in the longitudinal direction of the optical laminate; and peeling off a surface protective film temporarily attached to a polarizer while transporting the optical laminate. In an embodiment of the present invention, the surface protective film is peeled off in a state in which the extension direction of cracks in the polarizer forms an angle of 30° or more and less than 180° with respect to the transport direction.
[0046] For example, when the optical laminate is transported with the protective layer facing up, and the direction in which the crack extends when viewed from the top (protective layer side) is at an angle of 30° or more and less than 180° to the transport direction, the surface protective film may be peeled off while the optical laminate is transported in this state. When the optical laminate is one of the optical laminates described in items A to D above, the direction in which the crack extends is at an angle of 30° to 150° to the transport direction when viewed from either side (protective layer side or surface protective film side). Therefore, the surface protective film of such an optical laminate can be easily peeled off regardless of the state (stacking order) during transport.
[0047] For example, when the optical laminate is transported with the protective layer facing upward and the direction of crack extension when viewed from the upper side (protective layer side) is at an angle of more than 0° and less than 30° with respect to the transport direction, peeling off the surface protective film while transporting the optical laminate in this state often causes peeling failure. In this case, peeling failure can be suppressed by rewinding the optical laminate. Specifically, the optical laminate is once wound into a roll, and then unwound again to transport in the opposite direction. This allows the surface protective film to be peeled off in a state in which the direction of crack extension is at an angle of 30° or more and less than 180° with respect to the transport direction. For example, when the direction of crack extension when viewed from the upper side (protective layer side) is at an angle of 15° with respect to the transport direction, rewinding causes the direction of crack extension when viewed from the upper side (protective layer side) to be 165° with respect to the transport direction. That is, even if the optical laminate does not satisfy the requirements of the embodiment of the present invention, peeling failure can be suppressed by rewinding.
[0048] When peeling off the surface protection film, it is only necessary to control the direction in which the crack extends and the transport direction, and the surface protection film may be peeled off on the upward side (the optical laminate may be transported in a state in which it is positioned on the upward side) or on the downward side (the optical laminate may be transported in a state in which it is positioned on the downward side).
[0049] After the surface protective film is peeled off, various optical functional layers according to the purpose are laminated on the polarizer surface and / or the protective layer surface of the protective layer / polarizer laminate, and cut to a predetermined size (typically, a size corresponding to an image display device) at an appropriate time to obtain a polarizing plate or an optical film including a polarizing plate as a final product. The optical functional layers may be laminated by roll-to-roll, or may be cut to a predetermined size and then laminated. When a plurality of optical functional layers are laminated, some of them may be laminated by roll-to-roll, and the rest may be cut to a predetermined size and then laminated. EXAMPLES
[0050] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. Various measurement methods in the examples and comparative examples are as follows. Furthermore, unless otherwise specified, "parts" and "%" are based on weight.
[0051] (1) Indentation hardness Using a nanoindenter (manufactured by Hysitron Inc., "Triboindenter"), measurements were performed by a nanoindentation method under the following measurement conditions. Specifically, the probe (indenter) of the nanoindenter was pressed into the surface of the polarizer of the polarizing plate obtained in the Examples and Comparative Examples, and calculations were performed from the displacement-load hysteresis curves according to the following formula. Indentation hardness (GPa) = Pmax / A where Pmax is the maximum load obtained from the displacement-load hysteresis curve, and A is the contact projected area between the indenter and the polarizer. (Measurement conditions) Measurement method: Single indentation method ·Measurement temperature: 25℃ Push-in speed: approx. 2nm / sec Indentation depth: approx. 300 nm Indenter used: Diamond, Berkovich type (triangular pyramid type)
[0052] (2) Peeling off the surface protection film The surface protective film was peeled off from the slit long optical laminate obtained in each of the Examples and Comparative Examples while conveying the optical laminate. The state at that time was visually observed and evaluated according to the following criteria. ○ (Good): The surface protection film was peeled off without any problems. × (bad): At least a part of the polarizer peeled off together with the surface protective film.
[0053] (3) Edge bleaching From the optical laminates (polarizing plates) obtained in the examples and comparative examples, test pieces (50 mm x 50 mm) were cut out with two opposing sides in the stretching direction of the polarizer and in the direction perpendicular to the stretching direction, and the test pieces were attached to an alkali-free glass plate with an adhesive to prepare a measurement sample. The measurement sample was left in an oven at 65°C and 95% RH for 240 hours to heat and humidify it, and then placed in a cross-Nicol state with a standard polarizing plate, and the state of edge discoloration of the polarizer was examined using a microscope. Specifically, the amount of discoloration from the polarizer edge (edge discoloration amount: μm) was measured. An Olympus MX61L microscope was used to measure the edge discoloration amount from an image taken at a magnification of 10 times. The average value of the edge discoloration amount a in the stretching direction and the edge discoloration amount b in the direction perpendicular to the stretching direction was taken as the edge discoloration amount. The evaluation criteria for the edge discoloration amount are as follows. The evaluation results are shown in Table 1. ○ (Good): Edge discoloration amount is 400μm or less × (Fail): Edge discoloration amount is greater than 400 μm
[0054] [Production Example 1] 1. Preparation of Polarizer As a thermoplastic resin substrate, a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a Tg of about 75° C. was used, and one side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched 3.0 times in the longitudinal direction (machine direction) in an oven at 140° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the finally obtained polarizer would be the desired value (dyeing treatment). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4% by weight, potassium iodide concentration: 5% by weight) at a liquid temperature of 64°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 3 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, the film was dried in an oven maintained at about 90° C. while being brought into contact with a SUS heated roll whose surface temperature was maintained at about 75° C. (drying shrinkage treatment). In this manner, a polarizer P1 having a thickness of 5.5 μm was formed on the resin substrate, and a long polarizing plate having a resin substrate / polarizer P1 structure was obtained. The polarizer P1 had a single transmittance Ts of 43.0% and an indentation hardness of 0.688 GPa.
[0055] [Production Example 2] A long polarizing plate having a resin substrate / polarizer P2 structure was obtained in the same manner as in Example 1, except that the stretching temperature in the auxiliary air stretching treatment was 130° C., the stretching ratio was 2.4 times, and the temperature of the boric acid aqueous solution in the underwater stretching treatment was 70° C. The polarizer P2 had a single transmittance Ts of 43.0% and an indentation hardness of 0.646 GPa.
[0056] [Example 1] 1. Preparation of optical laminate An HC-TAC film was attached to the surface (opposite side to the resin substrate) of the polarizer P1 of the polarizing plate obtained in Production Example 1 by roll-to-roll bonding via an ultraviolet-curable adhesive. The HC-TAC film was a film in which an HC layer (7 μm thick) was formed on a triacetyl cellulose (TAC) film (25 μm thick), and the TAC film was attached to the polarizer side. Next, the resin substrate was peeled off to obtain a long polarizing plate having a configuration of HC layer / TAC film (protective layer) / polarizer P1. A surface protective film having a configuration of PET substrate (50 μm) / adhesive layer (10 μm) was attached to the surface of the polarizer P1 of the obtained polarizing plate by roll-to-roll bonding, and a long optical laminate having a configuration of HC layer / TAC film (protective layer) / polarizer P1 / surface protective film was obtained.
[0057] 2. Slitting the optical laminate The optical laminate obtained above was conveyed by a roll, and both ends in the width direction of the optical laminate were slit (cut) at 30 mm from each end of the polarizer using a slit blade as shown in Fig. 3. The taper angle of the cutting blade was 40°, and the conveying tension when slitting the optical laminate was 350 N. Furthermore, the contact pressure between the cutting blade and the receiving blade when slitting was 5 N, the overlap length L between the cutting blade and the receiving blade was 0.24 mm, and the rotation speed of the cutting blade was 102% of the conveying speed of the optical laminate.
[0058] As described above, a slit long optical laminate was obtained. In the obtained optical laminate, cracks were formed at the polarizer ends. When the optical laminate was viewed from the protective layer (HC layer) side, the direction in which the cracks extended was 80° to the conveying direction of the optical laminate, and the average length of the cracks was 825 μm. The obtained optical laminate was subjected to the above evaluations (2) and (3). The results are shown in Table 1.
[0059] [Examples 2 to 3 and Comparative Examples 1 to 3] A slit long optical laminate was obtained in the same manner as in Example 1, except that a polarizer shown in Table 1 was used, and the taper angle of the cutting edge of the slit blade and the transport tension during slitting of the optical laminate were changed as shown in Table 1. The obtained optical laminate was subjected to the same evaluation as in Example 1. The results are shown in Table 1. In the section "Removal of surface protective film" in Table 1, "as is" indicates that the surface protective film was peeled off while the optical laminate was transported in the same state, and "rewound" indicates that the optical laminate was rewound to reverse the transport direction, and then the surface protective film was peeled off.
[0060] [Table 1]
[0061] [evaluation] As is clear from Table 1, according to the examples of the present invention, even when the optical laminate contains a polarizer with a high degree of orientation, peeling failures can be suppressed when peeling off the surface protective film. Furthermore, as is clear from a comparison between Comparative Example 1 and Comparative Example 2, when the optical laminate contains a polarizer with a low degree of orientation, the problem of peeling failures depending on the direction in which the cracks extend does not occur. However, such polarizers have a problem in that the edge discoloration is large in a high-temperature and high-humidity environment. [Industrial Applicability]
[0062] The optical laminate according to the embodiment of the present invention can be suitably used as an intermediate for a polarizing plate or an optical film including a polarizing plate. The polarizing plate and the optical film obtained from the optical laminate according to the embodiment of the present invention can be suitably used in an image display device (typically, a liquid crystal display device or an organic EL display device). [Explanation of symbols]
[0063] 11 Polarizer 12 Protective layer 20 Surface protection film 100 Optical laminate
Claims
1. A long optical laminate, The polarizer includes a polarizer, a protective layer provided on one side of the polarizer, and a surface protective film temporarily and peelably attached to the other side of the polarizer, The indentation hardness of the polarizer is 0.65 GPa or more, A crack of 50 μm to 5000 μm is formed at an end portion in the width direction of the polarizer, The direction in which the crack extends is 30° to 150° with respect to the longitudinal direction. Optical laminate.
2. The optical laminate according to claim 1 , wherein the polarizer has an indentation elastic modulus of 9.5 GPa or less.
3. The optical laminate according to claim 2 , wherein the orientation function of the polarizer is 0.30 or more.
4. A roll of an optical laminate comprising the optical laminate according to claim 1 wound therein.
5. Transporting the optical laminate according to any one of claims 1 to 3 in a longitudinal direction of the optical laminate; and peeling off the surface protective film while transporting the optical laminate; The surface protective film is peeled off in a state where the extension direction of the crack forms an angle of 30° or more and less than 180° with respect to the conveyance direction. A method for manufacturing a polarizing plate.
6. A method for transporting a long optical laminate having a polarizer, a protective layer provided on one side of the polarizer, and a surface protective film temporarily and peelably attached to the other side of the polarizer, in a long direction of the optical laminate; and peeling off the surface protective film while transporting the optical laminate; The indentation hardness of the polarizer is 0.65 GPa or more, A crack of 50 μm to 5000 μm is formed at an end portion in the width direction of the polarizer, The extension direction of the crack is greater than 0° and less than 30° with respect to the conveyance direction of the optical laminate, The peeling of the surface protective film includes rewinding the optical laminate to reverse the transport direction of the optical laminate, and then peeling the surface protective film in a state in which the extension direction of the crack forms an angle of 30° or more and less than 180° with respect to the transport direction. A method for manufacturing a polarizing plate.
Citation Information
Patent Citations
Method and device of cutting laminate film, and method of manufacturing optical display device
JP2011183514A
Polyester film roll and production method of the same
JP2014180716A
Method for manufacturing polarizing plate
JP2017021315A
Manufacturing method of resin film roll
JP2020001382A
Method for manufacturing optical laminate
JP2020160231A